Leisure consumption in cricket: devising a model to contrast forms and time preferences. Issue 4 (3rd July 2016) - Pritchard, Adrian; Kharouf, Husni
Abstract : A large body of research exists on the motivation to follow sporting and leisure events. However, the main focus of these studies has been on those who attend events (direct consumers). Little research has extended the investigation of sporting and leisure consumption to include those who consume sport by other means such as the media (indirect consumers) and their scheduling preferences. With the growth of indirect consumption and its importance from both a finance and marketing perspective, this is an area of increasing interest in sports and leisure management. The purpose of this paper is to examine the consumption of sport in the UK and time and form preferences of spectators. We develop and validate a four-dimensional model to measure spectators' consumption, empirically testing it using 632 questionnaires in the context of cricket. Our findings show that although there was a stronger preference for direct consumption, there was a greater engagement in indirect consumption forms. A number of these activities, such as following the sport on the Internet are peripheral to the actual game and complement consumption of the match. A further finding of the research was that weekend consumption was most favoured by those who were more involved in the sport as club members. They expressed a stronger preference for Friday evening and Sunday scheduling for two different competitions.